Perceived Cultural Congruence, Place Attachment, and Intention to Participate in Coastal Community-Based Tourism Revitalization - Batubara, Soulthan Saladin; Insan, Muhammad Yalzamul; Yanti, Eli Delvi; Pratiwi, Shella (International Review of Management and Marketing, 2026)
This study examines how residents’ perceived cultural congruence with community-based tourism (CBT) initiatives influences their place attachment and their intention to engage in coastal tourism revitalization. A quantitative cross-sectional survey was conducted with 373 adult residents in Medan, North Sumatera, Indonesia. Partial least squares structural equation modeling (PLS-SEM) was used to test the hypothesized relationships, with place attachment operationalized as a reflective higher-order construct encompassing place identity, place affect, and place dependence. Results shod that perceived cultural congruence had a strong positive effect on place attachment (β = 0.627, f² = 0.648, p < 0.001) and a significant direct effect on intention to participate (β = 0.130, p = 0.008). Place attachment positively predicted intention to participate (β = 0.557, f² = 0.323, p < 0.001) and partially mediated the relationship between cultural congruence and participation (indirect β = 0.349, p < 0.001; total effect β = 0.479). The model explained 39.3% of variance in place attachment and 41.5% in intention to participate. Path coefficients were stable across residents with shorter and longer residential histories. Drawing on self-congruity theory and place attachment theory, this study is among the first to establish perceived cultural congruence as a substantively strong antecedent of place attachment and participatory intentions in a coastal CBT revitalization context. It advances resident-centered theorization of CBT by empirically confirming a cultural alignment to place bonding to participation pathway, extends self-congruity theory beyond destination loyalty and word-of-mouth to collective civic engagement, and offers actionable guidance for culturally sensitive tourism governance.